Pengaruh Komitmen Organisasional dan Keterlibatan Kerja Terhadap Hubungan Antara Etika Kerja Islam dengan Sikap Terhadap Perubahan Organisasi - Indira Januarti; Ashari Bunyaanudin (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2006)
This research examines the influence of organizational commitment and the involve¬ment in work to the relation between Islamic work ethics and attitude to organiza¬tional change. The samples are 32 lecturers and 31 accountant staff. Linear regression and absolute ap¬proach is used to test the effect of job involvement and organizational com¬mitment.The results of this research show that Islamic work ethics do not affect the attitude toward organizational change directly. The involvement in job has strong influence to the rela¬tion between Islamic work ethics and attitude to organizational change, while organiza¬tional com¬mit¬ment does not have strong influence to the relation between Islamic work ethics and attitude toward organizational change.Keywords: Islamic work ethics, job involvement, organizational commitment, attitude to organiza¬tional change.